Cover Picture: Unexpected Behavior of the Heaviest Halogen Astatine in the Nucleophilic Substitution of Aryliodonium Salts (Chem. Eur. J. 35/2016). Issue 35 (15th June 2016) - Guérard, François; Lee, Yong‐Sok; Baidoo, Kwamena; Gestin, Jean‐François; Brechbiel, Martin W.
Abstract : Despite 75 years having passed since its discovery, the heaviest halogen and one of the rarest of all elements, astatine, apparently still has surprises in store regarding its chemical properties. For example, astatine reactivity had been generally extrapolated from neighboring iodine, but experiments have often yielded unexpected results. In an investigation of the nucleophilic substitution of aryliodonium salts by heavy halogenides, astatine once again demonstrates novelty, with reaction kinetics being much faster than the anticipated trend within the halogen series. More information can be found in the Full Paper by F. Guérard, et al. onpage 12332 ff.